Phylogeny of Tacca (Taccaceae) and traits in reproductive structures, with description of a new Bornean species - Sin Yeng Wong; Kek Shen Chua (Society for Indonesian Biodiversity, 2019)
Abstract. Wong SY, Chua KS. 2019. Phylogeny of Tacca (Taccaceae) and traits in reproductive structures, with description of a new Bornean species. Biodiversitas 20: 3096-3118. A phylogenetic study of 16 of the c. 20 Tacca species is presented using nuclear ITS and plastid matK gene regions. Tacca leontopetaloides and T. maculata are a sister clade to the rest of the Tacca species. Tacca palmata and T. palmatifida are strongly supported together in a clade with this clade sister to T. bibracteata and T. plantaginea. All endemic Bornean taxa except T. bibracteata formed a derived clade together with non-Bornean T. cristata and T. sumatrana. The Bornean taxa are separated into three clades with T. borneensis sister to the other two clades. Twelve morphological characteristics are coded and mapped onto the Maximum Parsimony tree to elucidate potential evolutionary patterns. Results indicated shifts from a geophytic (irregularly-) seasonally dormant to an evergreen mesophytic habit, a decompound to a simple leaf blade, a long to a short peduncle, green to dark-colored inflorescences, numerous to few inner bracts, bracteoles, and flowers, and a low to an increased number of ovules. Within the Bornean taxa, there is a reversal from showy bracts and elaborate inflorescences to less showy bracts and simplified inflorescences. Tacca cristata Jack is resurrected from within T. integrifolia Ker Gawl. sensu Drenth. A new species, Tacca havilandii S.Y.Wong & K.S.Chua from Borneo is described.